Increasing the Concentration of School Holidays in Early Childhood - Ulfadhilah, Khairunnisa (JOYCED: Journal of Early Childhood Education, 2024)
It is very important for fathers and mothers to train their children to focus from an early age because many fathers and mothers make mistakes when introducing basic learning to their children but forget to teach them how to train their children's focus first. If children are used to practicing focus from an early age, they will easily accept various stimulation and basic learning that parents and mothers give their children at home, and children will get used to good focus. Training children to focus is not easy, and it cannot be done quickly, it needs to be gradual and takes time, so parents need to be patient so that children are able to focus well, which will affect the child's growth and development at home and at home. The research method uses descriptive qualitative so that it can describe the results of the research that has been carried out by the author and the research location at PAUD An-Nur. The data collection technique was direct observation at An-Nur PAUD, after which the author conducted interviews and documentation. It is hoped that the results of this research will serve as a guide for prospective mothers and fathers and those who are already fathers and mothers in educating their children and being able to train their children to focus from an early age because children's focus is related to concentration so that they get used to being at home with their fathers and mothers.